2022
DOI: 10.1038/s41467-022-32992-9
|View full text |Cite
|
Sign up to set email alerts
|

The AAA+ ATPase RavA and its binding partner ViaA modulate E. coli aminoglycoside sensitivity through interaction with the inner membrane

Abstract: Enteric bacteria have to adapt to environmental stresses in the human gastrointestinal tract such as acid and nutrient stress, oxygen limitation and exposure to antibiotics. Membrane lipid composition has recently emerged as a key factor for stress adaptation. The E. coli ravA-viaA operon is essential for aminoglycoside bactericidal activity under anaerobiosis but its mechanism of action is unclear. Here we characterise the VWA domain-protein ViaA and its interaction with the AAA+ ATPase RavA, and find that bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 62 publications
0
13
1
Order By: Relevance
“…S2 ) and no advantage was associated with RavA-ViaA complex for growth on fumarate. Recently, we reported that RavA-ViaA localizes to the inner membrane where it interacts with lipids and the lipid-binding properties of the RavA-ViaA complex were found to be necessary for AG sensitization under fumarate respiration ( 35 ). Thus, it seems a reasonable hypothesis to propose that the RavA-ViaA complex acts on the membrane to optimize function of some of the respiratory chains synthesized by E. coli , such as that involving Frd.…”
Section: Discussionmentioning
confidence: 99%
“…S2 ) and no advantage was associated with RavA-ViaA complex for growth on fumarate. Recently, we reported that RavA-ViaA localizes to the inner membrane where it interacts with lipids and the lipid-binding properties of the RavA-ViaA complex were found to be necessary for AG sensitization under fumarate respiration ( 35 ). Thus, it seems a reasonable hypothesis to propose that the RavA-ViaA complex acts on the membrane to optimize function of some of the respiratory chains synthesized by E. coli , such as that involving Frd.…”
Section: Discussionmentioning
confidence: 99%
“…AAA+ containing MoxR proteins cooperate with other VWA proteins to insert metal cofactors into substrate molecules [137][138][139]. In E. coli, this cooperation is exemplified by the concerted actions of MoxR unfoldase RavA with VWA protein ViaA, which modify cellular sensitivity to aminoglycosides antibiotics (presumably when they bind to bacterial ribosomes), or target the NADH:ubiquinone oxidoreductase-I as CI homolog, and the fumarate reductase respiratory complex [140][141][142]. RavA is also known for its impact on PLP-dependent lysine decarboxylase, a crucial enzyme for the generation of ornithine-derived polyamines that serve to stabilize RNA structure [143][144][145][146].…”
Section: The Putative Role Of Clpp-dependent Vwa8 For the Mtlsumentioning
confidence: 99%
“…Structural work revealed that RavA and ViaA interact with each other [13], and form a complex with a third partner, LdcI (or CadA) [12,13]. It was also shown that the RavA-ViaA complex interacts with phospholipids at the inner membrane [14].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of ravA-viaA genes in AG susceptibility was originally identified by independent approaches in different proteobacteria, Escherichia coli [11] and Vibrio cholerae [15]. In E. coli, overexpression of ravA-viaA sensitizes to gentamicin, and its deletion was shown to increase AG resistance [11,16] but only in anaerobic conditions and low energy state [14,17]. In V. cholerae, the ravA-viaA operon (VCA0762-VCA0763) is also involved in the response to low doses (below MIC, or sub-MIC) of AGs, this time in aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%